2017
DOI: 10.1111/1759-7714.12493
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on the relationship between zinc deficiency, related microRNAs, and esophageal carcinoma

Abstract: Esophageal cancer (EC) is a common malignant tumor of the gastrointestinal tract with a high incidence in China. Zinc (Zn) deficiency is a key risk factor for the occurrence and development of EC and affects progression by regulating microRNA (miRNA, miR) expression. In addition, the dysregulation of miRNAs is accompanied by the dysregulation of their target genes in EC. In this paper, we review the potential molecular mechanisms between Zn deficiency and EC with the aim of providing new strategies and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…EC is one of the most common cancers worldwide [1,2]; due to a high incidence of recurrence, its prognosis is poor [3]. miRNAs play a critical role in regulating tumorigenesis and metastasis of EC [4,5], and some miRNAs have been identified as prognostic markers or potential therapeutic targets [6,7]. miRNAs can act as either oncogenes or tumor suppressors to modulate growth, angiogenesis, drug or chemoresistance, invasion, and metastasis of malignant cells [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…EC is one of the most common cancers worldwide [1,2]; due to a high incidence of recurrence, its prognosis is poor [3]. miRNAs play a critical role in regulating tumorigenesis and metastasis of EC [4,5], and some miRNAs have been identified as prognostic markers or potential therapeutic targets [6,7]. miRNAs can act as either oncogenes or tumor suppressors to modulate growth, angiogenesis, drug or chemoresistance, invasion, and metastasis of malignant cells [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…There is a link between cancer occurrence and inflammatory factors induced by zinc deficiency [ 8 ]. Many researchers have focused on the ZD-related tumorigenesis on esophageal and gastric cancers [ 23 , 24 ]. However, its influences on colon tumorigenesis and its related mechanism remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional intervention also gives supportive treatment by providing adequate micronutrients. It has been shown that vitamin C, zinc, and vitamin B has been depleted in cancer patients, and correlated with anemia [11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, vitamin A is also known to increase epithelial cell formation and collagen deposition by fibroblasts. Therefore, vitamin A is also recommended for open chronic wounds 12 .…”
Section: Discussionmentioning
confidence: 99%